1999
DOI: 10.1210/endo.140.12.7288
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Gene Expression in the Brain and Pituitary Gland

Abstract: The adipocyte-derived hormone, leptin, and its receptor, are now known to be integral components of a physiological signalling system that regulates fuel stores and energy balance. Constitutive leptin expression has been demonstrated only in adipose tissue, placenta and stomach. We have used RT-PCR to show that leptin mRNA is selectively transcribed in specific areas of rat brain and pituitary, and in a rat glioblastoma cell line. Using immunocytochemistry we have also shown leptin protein immunoreactivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
1
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(145 citation statements)
references
References 0 publications
7
127
1
10
Order By: Relevance
“…44 Several other genes for which placental methylation has been associated with infant health are also expressed in the brain, such as HTR2A, 45 NR3C1, 46 FKBP5, 47 and LEP. 48 Epigenetic regulation by the placenta may influence these important neuropeptides that direct the development and function of the fetal brain. Additionally, it is possible that the DNA methylation patterns in the placenta are indicative of those within the fetal brain, thus making the placenta a surrogate tissue.…”
Section: Discussionmentioning
confidence: 99%
“…44 Several other genes for which placental methylation has been associated with infant health are also expressed in the brain, such as HTR2A, 45 NR3C1, 46 FKBP5, 47 and LEP. 48 Epigenetic regulation by the placenta may influence these important neuropeptides that direct the development and function of the fetal brain. Additionally, it is possible that the DNA methylation patterns in the placenta are indicative of those within the fetal brain, thus making the placenta a surrogate tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In hippocampal neurons, the expression of leptin receptors is also reportedly influenced by fasting [8]. Several studies have also demonstrated expression of leptin mRNA and protein throughout the CNS, suggesting that leptin may be released locally from specific neuronal populations [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent works indicate that leptin gene is also expressed in placenta (Senaris et al 1997), stomach (Bado et al 1998), heart (Matsui et al 2007), skeletal muscle (Wang et al 1998), and mammary gland (Smith-Kirwin et al 1998). Morash et al (1999) also report that gene and protein of leptin are expressed in rat cortex, cerebellum, hypothalamus, and pituitary gland in the CNS (Morash et al 1999). Either overexpression or lack of leptin can result in phenotypic abnormalities, such as obesity (Hsing et al 2007) or hypertension (Tumer et al 2007).…”
Section: Introductionmentioning
confidence: 99%